MEMAHAMI KAEDAH AL-KHURUJ MIN AL-KHILAF - Maizuddin M. Nur (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2013)
Rules of fiqh as an attempt to understand the general principles of fiqh andprovide convenience in applying the laws to the problems faced have beendeveloped by the jurists. One such principle is the principle of al-khuruju min al- al-khilaf. Some people categorize this as a rule of special rules in the field ofsiyasah. However, it appears that the practice of application of this rule fqihalmost penetrated all areas where there are differences of opinion. School leadershave practiced this method although by leaving the results of their ijtihad. However, this rule can not be applied as such. The application of this rule islimited to certain conditions. In connection with this issue methods oftransactions, seemingly not be applied strictly, because the field is experiencing avery special feature supple and flexible.